2011
DOI: 10.1002/hed.21833
|View full text |Cite
|
Sign up to set email alerts
|

Composition and architecture of biofilms on used voice prostheses

Abstract: The results give a better understanding of biofilm formation and can be used in further development to prevent biofilm formation on voice prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 38 publications
5
48
0
1
Order By: Relevance
“…On most prostheses studied by Buijssen et al (2012), bacteria were mostly located near the outermost surface of the biofilm and yeasts were predominantly located near or in the silicone rubber, demonstrating in-growing of yeast colonies. It has been suggested that the adhesion of bacteria to VPs is a prerequisite for subsequent colonization by yeasts (Neu et al, 1994a).…”
Section: Microbial Composition Of Biofilms On Voice Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…On most prostheses studied by Buijssen et al (2012), bacteria were mostly located near the outermost surface of the biofilm and yeasts were predominantly located near or in the silicone rubber, demonstrating in-growing of yeast colonies. It has been suggested that the adhesion of bacteria to VPs is a prerequisite for subsequent colonization by yeasts (Neu et al, 1994a).…”
Section: Microbial Composition Of Biofilms On Voice Prosthesesmentioning
confidence: 99%
“…(Neu et al, 1994b). Buijssen et al (2012) analysed 66 biofilms from several commonly used VP devices for their bacterial and fungal community population and reported the frequency with which micro-organisms were found as follows: C. albicans (77 %), C. tropicalis (52 %), Lactobacillus gasseri (96 %), Lactobacillus fermentum (73 %), Lactobacillus acidophilus (52 %) and streptococci (61 %). Lactobacilli were the predominant bacteria in voice prosthetic biofilms (Buijssen et al, 2007).…”
Section: Microbial Composition Of Biofilms On Voice Prosthesesmentioning
confidence: 99%
“…As a consequence, these devices are found to be rapidly colonized by bacteria and yeasts, leading to deterioration of the voice prosthesis. While the functional lifetime of voice prostheses in patients, ranges from several days to years; this period is most often cut short due to rapid biofilm formation, with an average in situ lifetime of around 3 to 4 months (Van Den Hoogen et al, 1996; van Weissenbruch et al, 1997; Op de Coul et al, 2000; Buijssen et al, 2012). Biofilms formed on silicone rubber voice prosthesis, largely comprise of yeast and bacterial spp.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that the interaction with bacterial strains, such as S. aureus enhances the initial steps of plaque formation and ultimate device failure. Still, to date the most commonly accepted decontamination methods are antifungal, [14, 16, 18] based on early studies conducted to characterize the effects of antifungal therapy on device life of VPs. Historical studies suggested promising results using various agents, [4, 6, 20] but the available level of evidence from early studies is low [27] and biofilms are several magnitudes more resistant to antifungal decontamination efforts than planktonic cells [28].…”
Section: Discussionmentioning
confidence: 99%